2018
DOI: 10.1073/pnas.1814856115
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 functions downstream of EDS1 to regulate TIR-NLR-mediated plant immunity in Nicotiana benthamiana

Abstract: SignificancePlants employ nucleotide-binding leucine-rich repeat (NLR) immune receptors to recognize pathogen effectors and to activate effector-triggered immunity (ETI). The Toll/IL-1 receptor-NLR (TNL) protein (Roq1) recognizes the effectors XopQ and HopQ1 in an Enhanced Disease Susceptibility 1 (EDS1)-dependent way in Nicotiana benthamiana. Interestingly, we found that the coiled-coil NLR protein N requirement gene 1 (NRG1) is required for activation of ETI by the TNLs Roq1 and Recognition of Peronospora pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
259
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(303 citation statements)
references
References 56 publications
16
259
1
3
Order By: Relevance
“…benthamiana NRG1, Qi et al . () indeed observed its oligo‐ or dimerization that relies on the CC domain. Furthermore, association between NRG1 and EDS1 also was detected using N .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…benthamiana NRG1, Qi et al . () indeed observed its oligo‐ or dimerization that relies on the CC domain. Furthermore, association between NRG1 and EDS1 also was detected using N .…”
Section: Discussionmentioning
confidence: 87%
“…Supporting this, a recent study showed the requirement of NRG1 in several TNL‐mediated, but not CNL‐mediated, immunity pathways in N . benthamiana (Qi et al ., ). By contrast, the ADR1 family is conserved among various plant species including monocots and eudicots (Collier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, as c . 20% of the ETI genes are still normally regulated in nrg1 (Qi et al ., ), SA signalling is probably not the only immune response still active in nrg1 mutants.…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, NRG1 is required for Roq1‐mediated HR and Roq1‐dependent bacterial resistance in N. benthamiana (Qi et al ., ). We speculate that ADR1 proteins, from the sister clade of NRG1, might complement the loss of NRG1s for some TIR‐NLRs, e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation